Influences on Body Size Perceptions Among Black Women in the Mississippi Delta. Issue 8 (November 2020) - Coleman, Lois; Bass, Martha; Cafer, Annie; Ford-Wade, Allison; Loftin, Mark
Purpose: To identify factors that influence Black women's body size perceptions Design: Interviews (cognitive mapping exercise) with 25 women; focus group with 7 additional women Setting: Mississippi Delta Participants: Thirty-two black women Measures: Influences on body size perceptions, body mass index, and body satisfaction Analysis: Interviewee maps were combined and condensed, using matrix addition and qualitative aggregation, to create a social map. The social map was presented to a focus group. A paired sample t test and descriptive statistics were run to assess weight perception accuracy and body satisfaction. Results: The initial social map contained 27 variables. Male preferences (87.5%) and appearance (64%) were believed by most participants to influence perceptions of body size. The focus group identified lack of encouragement, stress, and substance use as factors worth adding to the map. A statistically significant proportion of interviewees possessed an inaccurate weight perception, t (24) = 2.741, P < .05. Furthermore, 76% were dissatisfied with their current weight status and 80% desired a healthy body size. Conclusion: These findings provide practitioners with leverage points, beyond diet and physical activity, that may improve the efficacy of weight reduction interventions among black women. Considering the paucity of research regarding influences on body size perceptions, this study also provides researchers with participant-defined variables worthy of further examination.